2017
DOI: 10.1371/journal.pone.0186305
|View full text |Cite
|
Sign up to set email alerts
|

Use of immunohistochemical biomarkers as independent predictor of neoplastic progression in Barrett's oesophagus surveillance: A systematic review and meta-analysis

Abstract: IntroductionThe low incidence of oesophageal adenocarcinoma (EAC) in Barrett's oesophagus (BE) patients reinforces the need for risk stratification tools to make BE surveillance more effective. Therefore, we have undertaken a systematic review and meta-analysis of published studies on immunohistochemical (IHC) biomarkers in BE to determine the value of IHC biomarkers as neoplastic predictors in BE surveillance.Materials and methodsWe searched MEDLINE, EMBASE, Web of Science, CENTRAL, Pubmed publisher, and Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Another showed aberrant expression of p53 protein as a representative biomarker for prediction of neoplastic progression in BE [ 84 , 85 , 86 , 87 , 88 ]. Moreover, the TP53 mutation was found in 46% of patients with EAC progression [ 25 ], and reported to be associated with EAC progression with an OR of 3.18 (95% CI 1.68–6.03) [ 24 ] and an HR of 6.5 (95% CI 2.5–17.1) [ 89 ].…”
Section: Endoscopic Findings Showing Possible Predictive Biomarkermentioning
confidence: 99%
See 2 more Smart Citations
“…Another showed aberrant expression of p53 protein as a representative biomarker for prediction of neoplastic progression in BE [ 84 , 85 , 86 , 87 , 88 ]. Moreover, the TP53 mutation was found in 46% of patients with EAC progression [ 25 ], and reported to be associated with EAC progression with an OR of 3.18 (95% CI 1.68–6.03) [ 24 ] and an HR of 6.5 (95% CI 2.5–17.1) [ 89 ].…”
Section: Endoscopic Findings Showing Possible Predictive Biomarkermentioning
confidence: 99%
“…In an investigation of aspergillus oryzae lectin (AOL) as a new biomarker, it was demonstrated that not only abnormal DNA ploidy but also AOL could be used to identify BE patients who were most likely to develop dysplastic Barrett’s lesions [ 92 , 94 ]. Janmaat VT et al also reported that AOL was a useful biomarker to predict neoplastic progression, with an OR of 3.04 (95% CI 2.05–4.49) [ 24 ].…”
Section: Endoscopic Findings Showing Possible Predictive Biomarkermentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of molecular alterations of the Barrett’s epithelium could be a useful tool for risk stratification and prediction of response to therapy. For example, p53 aberrant expression (either absent or overexpression) detected by immunohistochemistry has been extensively studied, and could be as discriminative as the presence of LGD in the prediction of neoplastic progression [ 92 , 93 ]. Furthermore, analysis of the p53 expression pattern could help in improving the diagnostic accuracy of esophageal biopsies and lowering the rate of “indefinite for dysplasia” [ 94 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…Extensive studies have been conducted to explore the potential ancillary biomarkers for the diagnosis of BE-related dysplasia. Among them, p53 expression is the most promising diagnostic and prognostic marker [61,62]. In one study, positive p53 expression was found in 0% of BE ND cases, 9% of LGD cases, 55% of HGD cases, and 87% of those with EAC [63].…”
Section: Ancillary Biomarkers For Be Dysplasia and Early Stage Eacmentioning
confidence: 99%